Halycaea Cameron, 1903 (Hymenoptera: Braconidae, Doryctinae) from China with a key to world species - Tang, Pu; Belokobylskij, Sergey A.; van Achterberg, Cornelis; Chen, Xue-Xin (Zootaxa, 2012)
The Chinese Halycaea Cameron, 1903 (Doryctinae: Doryctini) from the Parasitic Hymenoptera Collection of ZhejiangUniversity were studied. The following taxa are described as new: subgenus Sinohalycaea subgen. nov. and four species,H. (S.) longitergum sp. nov., H. (H.) liui sp. nov., H. (H.) nigricoxis sp. nov., and H. (H.) wuzhiensis sp. nov. Megaproctusruficeps Smith, 1858 is considered as a senior synonym of H. erythrocephala Cameron, 1903 (syn. nov.). A key to all known species of Halycaea is provided.